Flood Disaster Mitigation Strategy in Kuala Lumpur - Puti Tiara Dewi; Iswandi Umar; Dedi Hermon; Febriandi (Postgraduate, University of Mataram, 2026)
In Malaysia, flash floods or major floods often occur in the capital city of Kuala Lumpur, flooding is a natural phenomenon that occurs when the volume of water flowing in rivers, lakes, or other bodies of water overflows onto land. The purpose of this study is to determine the level of flood vulnerability and determine flood mitigation strategies. This research is descriptive quantitative, which describes the phenomenon of flood disasters through mapping results. To produce a map of flood-prone areas, mapping was carried out using ArcGIS with a scoring method to see flood hazard vulnerability. The results of the flood vulnerability mapping study in Kuala Lumpur show critical conditions with almost 90% of the total area of 27.195.47 hectares categorized as vulnerable to very vulnerable to flooding. Analysis using the Analytic Hierarchy Process (AHP) method identified three priority mitigation strategies, namely Regulation (57.7%) as the highest priority which includes policy enforcement and implementation of MSMA, followed by Education (25.8%) to increase public awareness and preparedness, and Conservation (16.5%) through ecological rehabilitation and green infrastructure. The integration of these three strategies is necessary to create a comprehensive and sustainable flood mitigation framework, taking into account the high urbanization and climate change that continue to increase flood risks in the Kuala Lumpur metropolitan area.